The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pgen.1009758
|View full text |Cite
|
Sign up to set email alerts
|

CSYseq: The first Y-chromosome sequencing tool typing a large number of Y-SNPs and Y-STRs to unravel worldwide human population genetics

Abstract: Male-specific Y-chromosome (chrY) polymorphisms are interesting components of the DNA for population genetics. While single nucleotide polymorphisms (Y-SNPs) indicate distant evolutionary ancestry, short tandem repeats (Y-STRs) are able to identify close familial kinships. Detailed chrY analysis provides thus both biogeographical background information as paternal lineage identification. The rapid advancement of high-throughput massive parallel sequencing (MPS) technology in the past decade has revolutionized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
0
10
1
2
Order By: Relevance
“…In addition, multiple models could be built for the same sets of Y-STRs, based on different mutation rate estimates, for example if it is shown that the locus-specific mutation rates strongly differ in the population of interest. This method of investigation may become more precise over time as the number of addressable and well-characterized Y-STRs increases, for example by using massively parallel sequencing-based methods for data generation (Claerhout et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple models could be built for the same sets of Y-STRs, based on different mutation rate estimates, for example if it is shown that the locus-specific mutation rates strongly differ in the population of interest. This method of investigation may become more precise over time as the number of addressable and well-characterized Y-STRs increases, for example by using massively parallel sequencing-based methods for data generation (Claerhout et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…A massively parallel sequencing tool was developed to analyze 859 Y-SNPs to infer 640 Y haplogroups [ 473 ]. Another MPS tool, the CSYseq panel, targeted 15,611 Y-SNPs to categorize 1443 Y-sub-haplogroup lineages worldwide along with 202 Y-STRs including 81 slow, 68 moderate, 27 fast, and 26 rapidly mutating Y-STRs to individualize close paternal relatives [ 474 ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…The software is a good starting point as a secondary analysis option with additional flexibility for those interested in building custom solutions for their more specific needs beyond standard reports [17,46,47]. The offered modular tools and customization are ideal for stutter analysis or the visualization of stutter restoration to the respective parent allele [48].…”
Section: Fdstoolsmentioning
confidence: 99%